Why do Indian States Differ in Their Infrastructure Development? - Timilsina, Govinda R. (The World Bank, 2022)
The literature suggests that one of the main factors behind the interstate inequality in economic development in India is the variation in the level of infrastructure development. However, unequal infrastructure development across the Indian States is less understood. This study empirically analyzes various factors (economic, fiscal, demographic, social, institutional, and political) to explain interstate infrastructure inequality using a panel data set for 18 states in India between 2004 and 2020. Employing the principal component analysis technique, three separate infrastructure indices are developed for physical, social, and financial infrastructures. The relationship of each index with its explanatory variables is estimated using System Generalized Method of Moments. The results show that economic factors? including economic performance, financial development, investment, and economic structure?are more influential on physical infrastructure. For social infrastructure, in addition to economic factors, fiscal and demographic factors are more influential. Meanwhile, economic and demographic factors are found to drive financial infrastructure. Financial development fosters physical infrastructure, while its impact on social infrastructure is weak
Keywords: Determinants, Infrasturcture Investment; Government Expenditure; Infrastructure Development; Infrastructure Economics and Finance; Infrastructure Expenditure